Adolescent (reactive) periodisation - Balyi, I. (2009)
This presentation focuses on reactive periodisation and the development of the 5Ss during adolescence, in particular during the sensitive period of peak height velocity (PHV). The workshop will present how to allow for optimal recovery and regeneration as well as skill development and how to adjust athletes programs as they progress through PHV.